2019
DOI: 10.3892/ijo.2019.4819
|View full text |Cite
|
Sign up to set email alerts
|

PLEKHO1 knockdown inhibits RCC cell viability in vitro and in vivo, potentially by the Hippo and MAPK/JNK pathways

Abstract: Renal cell carcinoma (RCC) is the most common type of kidney cancer. By analysing The Cancer Genome Atlas (TCGA) database, 16 genes were identified to be consistently highly expressed in RCC tissues compared with the matched para-tumour tissues. Using a high-throughput cell viability screening method, it was found that downregulation of only two genes significantly inhibited the viability of 786-O cells. Among the two genes, pleckstrin homology domain containing O1 (PLEKHO1) has never been studied in RCC, to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Examining the expression of genes within the ontology term Regulation of Cell Shape (GO: 0008360) provides insight into the mechanisms by which cell shape may be driving NP phenotype. While the expression profiles of the genes GNA13, BAMBI, PLEKHO1, SEMA4D, and EPB41 vary, the proteins for all five of these genes are implicated in intracellular pathways (eg, Wnt, TGF‐β, PI3K‐AKT, and Hippo) as well as cellular functions including control of cell shape, cell migration, response to hypoxia, regulation of cell viability, differentiation and production of ECM proteins 101‐110 . GNA13 (G Protein Subunit Alpha 13) is a member of the guanine nucleotide‐binding protein family and is known to be involved in numerous transmembrane signaling pathways including RhoA/ROCK signaling (Uniprot) as well as Wnt and Hippo pathways, 111,112 upstream of cellular processes including cell shape, actomyosin‐contractility, migration, and cytoskeletal remodeling 112,113 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the expression of genes within the ontology term Regulation of Cell Shape (GO: 0008360) provides insight into the mechanisms by which cell shape may be driving NP phenotype. While the expression profiles of the genes GNA13, BAMBI, PLEKHO1, SEMA4D, and EPB41 vary, the proteins for all five of these genes are implicated in intracellular pathways (eg, Wnt, TGF‐β, PI3K‐AKT, and Hippo) as well as cellular functions including control of cell shape, cell migration, response to hypoxia, regulation of cell viability, differentiation and production of ECM proteins 101‐110 . GNA13 (G Protein Subunit Alpha 13) is a member of the guanine nucleotide‐binding protein family and is known to be involved in numerous transmembrane signaling pathways including RhoA/ROCK signaling (Uniprot) as well as Wnt and Hippo pathways, 111,112 upstream of cellular processes including cell shape, actomyosin‐contractility, migration, and cytoskeletal remodeling 112,113 .…”
Section: Discussionmentioning
confidence: 99%
“…While the expression profiles of the genes GNA13, BAMBI, PLEKHO1, SEMA4D, and EPB41 vary, the proteins for all five of these genes are implicated in intracellular pathways (eg, Wnt, TGF-β, PI3K-AKT, and Hippo) as well as cellular functions including control of cell shape, cell migration, response to hypoxia, regulation of cell viability, differentiation and production of ECM proteins. [101][102][103][104][105][106][107][108][109][110] functioning of membrane proteins and cell adhesion molecules. [114][115][116] Differences observed in expression of these genes are illustrative of the complex regulation used by cells to sense and respond to their mechanical and biochemical environment.…”
Section: Upregulated Gene Setsmentioning
confidence: 99%
“…PLEKHO1 affects tumor cell proliferation and apoptosis. Downregulation of PLEKHO1 impairs RCC progression [ 27 ]. In our study, PLEKHO1 was found to be highly expressed in monocyte and DC.…”
Section: Discussionmentioning
confidence: 99%
“…Also, tribbles pseudokinase 3 (TRIB3) regulated tumor progression by activating the MAPK signaling pathway to accelerate the proliferation, migration, and invasion of RCC (Hong et al, 2019). Also, pleckstrin homology domain-containing O1 (PLEKHO1) might promote the development of RCC by the Hippo and MAPK/JNK pathways in vitro and in vivo (Yu et al, 2019). Also, miR-106 b could promote RCC progression by targeting Capicua through MAPK signaling (Miao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%